Analisis Penggunaan Blockchain Terhadap Transparansi dan Keamanan Laporan Keuangan Syariah - Hesty Rindiani; Era Yudistira; Thoyibatun Nisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of blockchain technology in enhancing the transparency and security of Islamic financial reporting. The research employs a descriptive quantitative approach with a library research design, examining journals, books, and regulations related to blockchain and Islamic accounting. The findings reveal that blockchain, with its characteristics of decentralization, transparency, and immutability, addresses the limitations of conventional financial reporting, which is often historical and prone to manipulation. A synthesis of previous studies also reinforces the view that blockchain adoption strengthens accountability, reliability, and compliance of financial reports with Islamic principles. This study contributes to the development of digital-based Islamic accounting theory and provides practical implications for Islamic financial institutions and regulators. However, its limitation lies in relying solely on literature review, suggesting that future research should empirically test the effectiveness of blockchain in Islamic financial reporting practices.